Evolutionary Conservation of 3-Iodothyronamine as an Agonist at the Trace Amine-Associated Receptor 1 - Cöster, Maxi (Eur Thyroid J, 2015)
OBJECTIVES: The trace amine-associated receptor 1 (Taar1) is a G(s) protein-coupled receptor activated by trace amines, such as β-phenylethylamine (β-PEA) and 3-iodothyronamine (T(1)AM). T(1)AM is an endogenous biogenic amine and thyroid hormone derivative that exerts several biological functions. However, the physiological relevance of T(1)AM acting via Taar1 is still under discussion. Therefore, we studied the structural and functional evolution of Taar1 in vertebrates to provide evidence for a conserved Taar1-mediated T(1)AM function. STUDY DESIGN: We searched public sequence databases to retrieve Taar1 sequence information from vertebrates. We cloned and functionally characterized Taar1 from selected vertebrate species using cAMP assays to determine the evolutionary conservation of T(1)AM action at Taar1. RESULTS: We found intact open reading frames of Taar1 in more than 100 vertebrate species, including mammals, sauropsids and amphibians. Evolutionary conservation analyses of Taar1 protein sequences revealed a high variation in amino acid residues proposed to be involved in agonist binding, especially in rodent Taar1 orthologs. Functional characterization showed that T(1)AM, β-PEA and p-tyramine (p-Tyr) act as agonists at all tested orthologs, but EC(50) values of T(1)AM at rat Taar1 differed significantly when compared to all other tested vertebrate Taar1. CONCLUSIONS: The high structural conservation of Taar1 throughout vertebrate evolution highlights the physiological relevance of Taar1, but species-specific differences in T(1)AM potency at Taar1 orthologs suggest a specialization of rat Taar1 for T(1)AM recognition. In contrast, β-PEA and p-Tyr potencies were rather conserved throughout all tested Taar1 orthologs. We provide evidence that the observed differences in potency are related to differences in constraint during Taar1 evolution.